Europeans and Americans of European origin show differences between their biological pathways related to the major histocompatibility complex - Vaulin, Andrey (2024)
In this study, we analysed biological pathway diversity among Europeans and Northern Americans of European origin, the groups of people that share a common genetic ancestry but live in different geographic regions. We used a novel complex approach for analysing genomic data: we studied the total effects of multiple weak selection signals, accumulated from independent SNPs within a pathway. We found significant differences between immunity-related biological pathways from the two groups. All identified pathways included genes belonging to the major histocompatibility complex (MHC) system, which plays an important role in adaptive immune responses. We suggest that the ways of evolution were different for the MHC-I and MHC-II gene groups at least in Europeans and Americans of European origin. We hypothesise that the observed variability between the two populations was triggered by selection pressures due to the different pathogen landscapes and pathogen loads on the two continents. Our findings can be important for epidemic prevention and control, as well as for analysing processes related to allergies, organ transplantation, and autoimmune diseases.